Optimization of Assignment of Rapid Train Stops: Example of the JR Nambu Line - Keiya OKADA; Ryuhei MIYASHIRO (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2012)
On many railway lines, not only local trains but also rapid trains are operated. Operating rapid trains can improve the convenience of the passengers, but that outcome strongly depends on the assignment of rapid train stops, the associated timetable, and the number of incoming and outgoing passengers at stops on the way. In particular, to fix assignment of rapid train stops is of great importance. Some previous studies have been conducted to determine optimal assignment of rapid train stops; however, they have relied on approximation methods such as genetic algorithms and local searches. In this study, an enumeration-based algorithm to find optimal assignment of rapid train stops is proposed. Taking actual origin-destination (OD) data of the JR Nambu line, which is a medium-scaled line with 25 stations in Japan, as an example, the proposed algorithm determines optimal assignment of rapid train stops and the associated timetable.